Biliary tract external drainage improves inflammatory mediators and pathomorphology of the intestine, liver, and lung in septic rats. Issue 3 (September 2018) - Liu, Yong-Jun; Sun, Qing; Chen, Juan; Chen, Min-Ying; Ouyang, Bin; Sun, Hua-Dong; Nie, Yao; Wang, Ping-Ping; Ma, Jie; Guan, Xiang-Dong
Abstract : BACKGROUND: To investigate the effect of biliary tract external drainage (BTED) on inflammatory mediators and pathomorphism of intestine, liver, and lung in septic rats. METHOD: 48 SD rats (n = 8 per group) were randomized into six groups: control, sepsis, sepsis plus BTED, normal bile (obtained from eight healthy rats), and septic bile infusion for 6 hours respectively to test the effects of BTED bile infusion on cytokines' expression and tissue injury in the intestine, liver, and lung of septic/normal rats. Co-cultivation of intestinal epithelial cells (IEC-6) with bile for 12 hours was performed to evaluate the potential cytotoxicity of septic bile. Survival rate for sepsis plus BTED rats was detected compared with sepsis without BTED group (n = 20 per group) at 24, 48, and 72 hours, respectively. RESULTS: BTED for 6 hours significantly reduced the mRNA expression levels of tumor necrosis factor alpha (TNF-α) and IL-1β (all p < 0.05 vs. sepsis group), whereas mRNA expression of TNF-α and IL-1β in the intestine was increased after 6 hours' septic bile infusion compared with normal bile infusion group (all p < 0.05). TNF-α concentration in septic bile was significantly higher than that in the control group ( p < 0.001). Tissue injury was significantly attenuated after 6 hours' BTED. CONCLUSIONS: BTED can significantly restrain the mRNA expression of TNF-α and IL-1β in the intestine, liver, and lung and attenuate histological damage in septic rats. Abstract : Supplemental digital content is available in the text.